Public relations for schools : a resource guide for principals - Lunblad, Sally S.; Stewart, G. Kent (Emerald Publishing Limited : Information Age Pub., 2005)
This handbook is for practitioners who lead public and private elementary schools, middle schools or high schools. While most school leaders are basically adept at public relations, this book serves as a reminder of the importance of good public relations and provides ready access to tools necessary to hone and refine public relations skills. In addition to important information about public relations, this handbook is replete with examples of good public relations practices.